A large-scale zebrafish gene knockout resource for the genome-wide study of gene function - Varshney, Gaurav K.; Lu, Jing; Gildea, Derek E.; Huang, Haigen; Pei, Wuhong; Yang, Zhongan; Huang, Sunny C.; Schoenfeld, David; Pho, Nam H.; Casero, David; Hirase, Takashi; Mosbrook-Davis, Deborah; et al. (Genome Research, 2013)
With the completion of the zebrafish genome sequencing project, it becomes possible to analyze the function of zebrafish genes in a systematic way. The first step in such an analysis is to inactivate each protein-coding gene by targeted or random mutation. Here we describe a streamlined pipeline using proviral insertions coupled with high-throughput sequencing and mapping technologies to widely mutagenize genes in the zebrafish genome. We also report the first 6144 mutagenized and archived F1's predicted to carry up to 3776 mutations in annotated genes. Using in vitro fertilization, we have rescued and characterized ∼0.5% of the predicted mutations, showing mutation efficacy and a variety of phenotypes relevant to both developmental processes and human genetic diseases. Mutagenized fish lines are being made freely available to the public through the Zebrafish International Resource Center. These fish lines establish an important milestone for zebrafish genetics research and should greatly facilitate systematic functional studies of the vertebrate genome.